GERAKAN EMANSIPASI RUHANA KUDDUS DALAM MEMPERJUANGKAN KESETARAAN PENDIDIKAN PEREMPUAN DI MINANGKABAU - Nur Farida Deliani; Nazhiratul Khairat; Kori Lilie Muslim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
At the beginning of the 19th century in Minangkabau, women just demanding to manage the household, they are not allowed to get the appropriate education and the high position of career. Because of this unlucky condition, some women in Minangkabau made a movement out of that oppression. One of the movement's doers is Ruhana Kuddus. In order to know the affection of Rohana Kuddus’s emancipation in her struggle for women’s education equality, these are the techniques of data collection and analysis is collecting the data, the main source is Scenting Melajoe newspaper, the second sources Are interviewing, book, journal, and all of the data about Ruhana Kuddus from the internet. Then criticizing of the sources, it can be internal and external critics. After that synthetic dan writing form (historiography). The results are incentive factors are religion value, traditional value, and social value. Obstructions factors are the illiteracies, the strict of traditional rules, the views on women, the empowerment of women and women’s skills.